INITIAL SKILLS TO BE DEVELOPED IN STUDENTS IN CHEMISTRY (American Journal of Pedagogical and Educational Research, 2024)
This article argues that students' generalized skills in chemistry should be viewed as a feature of action. That is, it has been shown that the generalization and assimilation of each formed skill is based on a certain rule.